Colombian women in two transnational films: building an image of woman - Silva Rodríguez, Manuel (Íkala, Revista de Lenguaje y Cultura, 2015)
This article describes and analyzes the representations of Colombian women in the films El arriero (2009) and Rabia (2009), both made as co-productions. The text suggests understanding co-production as a part of transnational space, and it follows, in its methodology, formulations from imagology and feminist studies. With such tools, the article seeks to establish which features serve to build images of women associated to Colombian nationality. Finally, the paper concludes that the pornographic gaze and the economy are crucial to the construction of those images.